PROGRAM PEMBERDAYAAN MELALUI LITERASI KESEHATAN DENGAN PENGELOLAAN OBAT MANDIRI DI DESA PERSATUAN - Abdulkadir, Widy Susanti; Keku, Indeks S. (Batara Wisnu : Indonesian Journal of Community Services, 2025)
The community empowerment program on health literacy with self-medication management in Persatuan Village, Pohuwato Regency, aims to improve public knowledge regarding the safe and effective management of medications. The background of this service stems from the low health literacy level in the community, particularly in medication management, which may lead to the risk of drug misuse and adverse health effects. The problem formulation addressed is the lack of understanding among the community about the proper use of medications, which necessitates education on self-medication management. The goal of this service is to enhance the understanding of the people in Persatuan Village through counseling and training on the correct and safe use of medications. The methods used consist of four stages: health literacy counseling, practical medication management training, post-training assistance, and evaluation. Counseling is conducted through interactive lectures and visual media, followed by practical training that provides simulations on medication management, as well as routine assistance to ensure the application of the knowledge. The results of this service show significant improvements in knowledge, with an increase ranging from 50% to 150% in pre-test and post-test scores. This program successfully enhanced the community’s understanding of the proper and safe management of medications. The conclusion of this service is that health literacy focused on self-medication management is effective in improving the community’s knowledge, and the sustainability of the program can be achieved by strengthening the role of local health cadres, integrating this activity into regular village health programs, and conducting ongoing monitoring and evaluation. The recommendation for the development of this program is to further integrate empowerment activities into other village health programs and involve more parties to support the program’s sustainability in the future.